Doing Decoloniality in the Writing Borderlands of the PhD. Issue 1 (25th September 2017) - McDowall, Ailie; Ramos, Fabiane
Abstract : This paper takes us into the Writing Borderlands, an ambiguous in-between space borrowed from Anzaldúa's concept of Borderlands, where we as PhD students are in a constant state of transition. We argue that theorising from a decolonial position consists of not merely using concepts around coloniality/decoloniality, but also putting its core ideas into practice in the 'doing' aspect of research. The writing is a major part of this doing. We enact epistemic disobedience by challenging taken-for-granted conventions of what 'proper' academic writing looks like. Writing from a universal standpoint — the type of writing prescribed in theses formats, positivist research methods and 'proper' academic writing — has been instrumental in promoting the zero-point epistemologies that prevail through Northern artefacts of knowledge. In other words, we write to de-link from the epistemological assumption of a neutral and detached observational location from which the world is interpreted. In this paper, we discuss the journey we take as PhD students as we attempt to delink and decolonise our writing. Traversing the landscape of the Writing Borderlands, different features arise and fall. Along the way, we come across forks in the road between academic training and the new way we imagine writing decolonially.